Metastatic Crohn′s disease of external genitalia - Panackel Charles; John Joseph; Krishnadas Devadas; Vinayakumar Kattoor (Wolters Kluwer Medknow Publications, 2008)
Metastatic Crohn′s disease is an uncommon extraintestinal manifestation of Crohn′s disease. Its hallmark features include the presence of cutaneous noncaseating granulomas that are noncontiguous with the gastrointestinal tract or fistula. We report a rare case of metastatic Crohn′s disease involving the external genitalia in a 14-year-old girl. Diagnosis was based on skin biopsy. Patient had complete recovery on treatment with oral and topical steroids along with azathioprine.